Analysis Of The Implementation Of The Subsidized Fertilizer Program In Gapoktan Gurun Raya - Atifa, Saydatul; Alfikri; Arnayulis; Lailatul Mubarokah, Syaima (JURNAL AGRIBISAINS, 2025)
This study aims to analyze the implementation of the subsidized fertilizer program in Gapoktan Gurun Raya, Nagari Gurun, Harau District, Lima Puluh Kota Regency. The focus of the study is the effectiveness of the program based on the principle of 6 Tepat (Quantity, Place, Price, Time, Type, and Quality). The method used is a qualitative approach with primary data collected through in-depth interviews, field observations, and structured questionnaires to 40 farmers who are members of 4 farmer groups in Gapoktan Gurun Raya. Secondary data was obtained from the Gapoktan archives and other related sources. The results of the study indicate that the implementation of the subsidized fertilizer program in Gapoktan Gurun Raya as a whole is quite effective with an average satisfaction of above 60% in almost all indicators. However, the "Right Place" indicator showed the lowest result (62.5%) which indicates limited accessibility of fertilizer distribution for farmers. In addition, the "Right Time" aspect also still needs to be improved to avoid delays in distribution that can disrupt farmers' planting schedules. Based on these findings, it is recommended to improve coordination between distributors and farmer groups, add distribution points that are easier to reach, and conduct regular evaluations of farmers' fertilizer needs. The results of this study are expected to contribute to improving the implementation of fertilizer subsidy policies in the agricultural sector.